2004
DOI: 10.2337/diacare.27.10.2299
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Population Management

Abstract: OBJECTIVE—Population-level strategies to organize and deliver care may improve diabetes management. We conducted a multiclinic controlled trial of population management in patients with type 2 diabetes. RESEARCH DESIGN AND METHODS—We created diabetic patient registries (n = 3,079) for four primary care clinics within a single academic health center. In the intervention clinic (n = 898), a nurse practitioner used novel clinical software (PopMan) to identify patients on a weekly basis with outlyin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
70
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 36 publications
3
70
1
Order By: Relevance
“…However, subgroup differences by age in testing and by race/ethnicity in HbA 1c testing and outcomes among disabled women suggest that subgroup-specific interventions may be needed to improve diabetes care. This is also consistent with a larger body of literature suggesting the lack of efficacy of global quality improvement programs for diabetes and hypertension (Grant et al, 2004;Murray et al, 2004;O'Connor et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…However, subgroup differences by age in testing and by race/ethnicity in HbA 1c testing and outcomes among disabled women suggest that subgroup-specific interventions may be needed to improve diabetes care. This is also consistent with a larger body of literature suggesting the lack of efficacy of global quality improvement programs for diabetes and hypertension (Grant et al, 2004;Murray et al, 2004;O'Connor et al, 2005).…”
Section: Discussionsupporting
confidence: 90%
“…Unfortunately, most approaches used to improve diabetes outcome measures have been ineffective in practice. These include: 1) reminding patients about appointments (5,6); 2) providing feedback information on patients to their treating physicians (7)(8)(9)(10), even when treatment recommendations for the patient were included (11,12); 3) case management (when the case manager could not make treatment decisions) (13,14); 4) physician education (15,16); and 5) multifaceted quality improvement interventions in the practice setting (17,18).…”
mentioning
confidence: 99%
“…Another study in 24 practices in Minnesota, which included a case manager function, showed improvements in both process and outcome 15 . Other interventions have resulted in improvement in process but not laboratory outcomes 8,10,16 . Systematic reviews suggest that quality improvement strategies in diabetes care produce modest results 45,46 .…”
Section: Discussionmentioning
confidence: 99%
“…The Chronic Care Model highlights the importance of a population-based approach; involving community, patients and providers; and information technology [4][5][6] . Various combinations of population management, practice support, and patient outreach have been used for diabetes care in a variety of settings with mixed results [7][8][9][10][11][12][13][14][15][16] . Many practice interventions for diabetes have been carried out in academic and urban centers.…”
mentioning
confidence: 99%